Explaining Gender-Based Selection Decisions: A Synthesis Of contextual and Cognitive Approaches - Perry, Elissa L.; Davis‐Blake, Alison; Kulik, Carol T. (Academy of Management Review, 1994)
In this article we integrate contextual and cognitive explanations for gender-based selection in the workplace; we also consider the implications of this integration for understanding gender segregation. We argue that decision makers' propensity to use applicant gender as a basis for hiring and promotion decisions varies systematically across organizational contexts. We explore specific ways in which organizational context influences decision makers' development and use of gender-associated schemas of typical jobholders. We also argue that the interaction between context and cognition may be partially responsible for the persistence of gender segregation. Finally, we discuss the implications of our approach for the practice of personnel selection and research on selection and gender segregation.